Maynila sa mga kuko ng liwanag - Jocson, Max.; Reyes, Luis.; Reyes, Ramon; Jarlego, Edgardo; Jarlego, Ike.; Del Mundo, Clodualdo; Manotok, Severino; De Leon, Miguel; Brocka, Lino.; Koronel, Hilda; Salvador, Lou.; Abuel, Tommy; et al. (Manila Cinema Artists, 1975)
Julio is a poor teenage fisherman who has lost track of his childhood sweetheart Ligaya in the busy streets of Manila. He goes to the jungles of the metropolis in order to find her.
"Mula sa nobelang Sa mga kuko ng liwanag ni Edgardo Reyes."
Original music, Max Jocson ; sound, Luis Reyes, Ramon Reyes ; editing, Edgardo Jarlego, Ike Jarlego, Jr. ; screenplay, Clodualdo del Mundo, Jr. ; producers, Severino Manotok, Jr., Miguel de Leon ; direction, Lino Brocka.
Hilda Koronel, Lou Salvador, Jr., Tommy Abuel, Rafael Roco, Jr.
Keywords: Urban poor -- Philippines -- Drama; Unfair labor practices -- Philippines -- Drama; Construction workers -- Philippines -- Drama; Prostitution -- Philippines -- Drama